The transport behaviour of microplastics in longitudinal mixing and hyporheic exchange under varied flow conditions - Chan, Hui Ling (2019)
Microplastics is an emerging pollutant that are increasingly detected in major rivers around the world. They are potentially harmful to the natural environment due to their toxicity and potential for bioaccumulation. Yet much of the plastics today remain “missing” as transport and sink mechanisms of plastics and microplastics has not been properly studied. This study develops a novel method to track microplastic movement where spherical Polyethylene (PE) microplastics of size ranging from 40 to 46µm is stained using Nile Red. The dispersion behaviour of microplastics is subsequently studied by predicting the longitudinal dispersion coefficient from the standard Advection-Dispersion (ADE) Model at uniform flow discharges, and with the addition of a weir. Stable fluorescence detection of the microplastics in the water is achieved. This method proves to be successful in tracking the temporal concentration distribution of microplastics in the flow, producing a similar dispersion curve to conventional dye tracers. A comparison of the microplastics coefficients with that of Rhodamine WT further reveals that Polyethylene microplastics disperses in a similar manner as Rhodamine in the water column. This marks the potential of using Rhodamine WT as a proxy to study the dispersion characteristics of microplastics in natural rivers.